Hydroxyl PAMAM dendrimer-based gene vectors for transgene delivery to human retinal pigment epithelial cells. Issue 9 (12th September 2014) - Mastorakos, Panagiotis; Kambhampati, Siva P.; Mishra, Manoj K.; Wu, Tony; Song, Eric; Hanes, Justin; Kannan, Rangaramanujam M.
Abstract : Hydroxyl PAMAM dendrimer-based gene vectors with tailored surface characteristics demonstrate improved cell uptake and transfection of human RPE cells. Abstract : Ocular gene therapy holds promise for the treatment of numerous blinding disorders. Despite the significant progress in the field of viral and non-viral gene delivery to the eye, significant obstacles remain in the way of achieving high-level transgene expression without adverse effects. The retinal pigment epithelium (RPE) is involved in the pathogenesis of retinal diseases and is a key target for a number of gene-based therapeutics. In this study, we addressed the inherent drawbacks of non-viral gene vectors and combined different approaches to design an efficient and safe dendrimer-based gene-delivery platform for delivery to human RPE cells. We used hydroxyl-terminated polyamidoamine (PAMAM) dendrimers functionalized with various amounts of amine groups to achieve effective plasmid compaction. We further used triamcinolone acetonide (TA) as a nuclear localization enhancer for the dendrimer-gene complex and achieved significant improvement in cell uptake and transfection of hard-to-transfect human RPE cells. To improve colloidal stability, we further shielded the gene vector surface through incorporation of PEGylated dendrimer along with dendrimer-TA for DNA complexation. The resultant complexes showed improved stability while minimally affecting transgene delivery, thus improving the translational relevance of this platform.